La protection maternelle - Anne-Laure Garcia (Glad!)
The notion of protection implies a differentiation between the protector and the protégé. This structuring opposition illustrates the binary and hierarchical characteristic of schemes of perception and appreciation. In order to shed light on the gendered relations fixed by forensic discourses about protection of women, this article analyzes the law texts about protection of mothers, that were adopted between 1945 and 1952 in France, in the FRG and in the GDR. Those three case studies point up the categorizations and the hierarchizations between the female figures fixed by those juridical discourses.